The Hoffnung Symphony Orchestra - Hoffnung, Gerard 1925-1959 (London The Hoffnung Partnership, 2000)
The fact that a multitude of individualists can be harnessed to produce a unified ensemble was to Hoffnung one of the miracles of music and helped inspire his cartoon of the full orchestra shown at the beginning of the book. In the cartoons that follow, one for each instrument, a whole gamut of emotions comes into play. Could the couple sharing the violin and the experience of playing it together be anything but in love? High-lighted are the hazards and dangers confronting players of cymbals and tubular bells, as are the shocks sometimes experienced by organists and harpists. Operating a wind-machine can be uncomfortable and sitting too close to a bass trombone positively painful. This book is informative to a high degree and supplies many chuckles per page.